Secrets of an Irrsistible Woman - Mckinney, Hammond Michelle (Harvest House Publishers, 1998)
Searching for LOVE$1! = (BThousands of women attribute finding Mr. Right and getting to the altar on time to this book. How do you find a good man? How do you know if he's "the one''? And then what do you do? In her honest and forthright style, singles counselor Michelle McKinney Hammond shares the wisdom she's gained from her own experiences and practical scriptural principles to reveal the nitty-gritty details of love and relationships$1! =s
Keywords: Man & Woman relationships; Mate selection; Non-Fiction; Women - Conduct of life